2009
DOI: 10.1111/j.1749-6632.2009.03927.x
|View full text |Cite
|
Sign up to set email alerts
|

desat1 and the Evolution of Pheromonal Communication in Drosophila

Abstract: The evolution of communication is a fundamental biological problem. The genetic control of the signal and its reception must be tightly coadapted, especially in interindividual sexual communication. However, there is very little experimental evidence for tight genetic linkage connecting the emission of a signal and its reception. In Drosophila melanogaster, desat1 is the first known gene that simultaneously affects the emission and the perception of sex pheromones. Our experiments show that both aspects of phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…QTL mapping studies on hybrids derived from closely related species, such as D. melanogaster and D. simulans, or D. mauritiana and D. sechellia, have implicated loci on the third chromosome associated with generating differences in cuticular hydrocarbon composition among species (Coyne et al 1994;Coyne 1996a,b;Coyne and Charlesworth 1997;Gleason et al 2005) and sensing different pheromonal signatures (McMahon et al 2002). Subsequent studies associated members of the desaturase gene family with sex-specific expression and the evolution of differences in cuticular pheromones between Drosophila species (Marcillac et al 2005a;Legendre et al 2008;Bousquet et al 2009;Shirangi et al 2009;Keays et al 2011;Pardy et al 2019).…”
Section: Evolution Of Pheromone-mediated Courtship Signalsmentioning
confidence: 99%
“…QTL mapping studies on hybrids derived from closely related species, such as D. melanogaster and D. simulans, or D. mauritiana and D. sechellia, have implicated loci on the third chromosome associated with generating differences in cuticular hydrocarbon composition among species (Coyne et al 1994;Coyne 1996a,b;Coyne and Charlesworth 1997;Gleason et al 2005) and sensing different pheromonal signatures (McMahon et al 2002). Subsequent studies associated members of the desaturase gene family with sex-specific expression and the evolution of differences in cuticular pheromones between Drosophila species (Marcillac et al 2005a;Legendre et al 2008;Bousquet et al 2009;Shirangi et al 2009;Keays et al 2011;Pardy et al 2019).…”
Section: Evolution Of Pheromone-mediated Courtship Signalsmentioning
confidence: 99%
“…All the CHs that have been identified as pheromones are unsaturated long-chain compounds, and some are sexually dimorphic: only females produce dienes, several of which induce male courtship, while males produce monoenes that have been shown to inhibit courtship from other males (Jallon 1984; Foley et al 2007; Wicker-Thomas 2007; Arienti et al 2010). Two desaturases are involved in CH production: the enzyme Desat1, is expressed in males and females, both in the oenocytes and in the fat body (Marcillac et al 2005b; Marcillac et al 2005a; Ueyama et al 2005; Bousquet et al 2009; Bousquet et al 2012), and DesatF , is specifically expressed in female oenocytes (Chertemps et al 2006). CHs not only play roles in inter-specific courtship, they also contribute to species isolation (Coyne et al 1994; Savarit et al 1999; Coyne et al 1999; Marcillac et al 2005c; Bontonou et al 2012).…”
Section: Sex Recognition and Male Behavioral Choicementioning
confidence: 99%
“…Gustatory neurons of the legs project to thoracic ganglia and the suboesophageal ganglion (SOG) (Possidente and Murphey, 1989), olfactory neurons to the glomeruli of the antennal lobes. A recent study has suggested that the desat1 gene involved in the biosynthesis of pheromones plays a role: a mutation in desat1 simultaneously altered both sex pheromone emission and perception in D. melanogaster (Bousquet et al, 2009). Moreover, although specific receptors and pheromones are playing an important role, intriguingly, the specificity of some of the responses may lie in the wiring and projections of specific neurons (see Section III.C).…”
Section: B Male-male Courtship or How To Discriminate Between Males mentioning
confidence: 99%